Makna yang Timbul dari Kesadaran Membayar Pajak Restoran - Alfian Suradiansyah; Ni Putu Eka Widiastuti; Alfida Aziz (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This research aims to gain an understanding of the meaning of restaurant tax on restaurant taxpayers in South Tangerang City. The method used in this research is a qualitative method with intepretive paradigm and phenomenology approach. The results of the research revealed that the informant had understood about their obligation to pay restaurant taxes to the local government. They understand that restaurant taxation is an obligation as citizens who set up a restaurant business in an area against the regional government which can be used as a source of regional revenue to finance the needs of local governments. The meaning of restaurant tax cannot be separated from their life background, character, culture and philosophy. Informants interpret restaurant taxes as a form of reciprocity to local governments, peace of business, contribute to the region and forming a sense of social responsibility.